Regulatory mechanism of a heat-activated retrotransposon by DDR complex in Arabidopsis thaliana - Niu, Xiaoying; Chen, Lu; Kato, Atsushi; Ito, Hidetaka (Frontiers in Plant Science, 2022)
The RNA-directed DNA methylation (RdDM) pathway plays an essential role in the transposon silencing mechanism; the DDR complex, consisting of DRD1, DMS3, and RDM1, is an essential component of the RdDM pathway. ONSEN, identified in Arabidopsis, is a retrotransposon activated by heat stress at 37 °C; however, studies on the regulation of ONSEN are limited. In this study, we analyzed the regulation of ONSEN activity by the DDR complex in Arabidopsis. We elucidated that loss of any component of the DDR complex increased ONSEN transcript levels. Transgenerational transposition of ONSEN was observed in the DDR-complex mutants treated with heat stress for 48 h. Furthermore, the DDR complex components DRD1, DMS3, and RDM1 played independent roles in suppressing ONSEN transcription and transposition. Moreover, we found that the duration of heat stress affects ONSEN activity. Therefore, the results of this study provide new insights into the retrotransposon regulatory mechanisms of the DDR complex in the RdDM pathway.